Variabilidade de isolados de Monosporascus cannonballus oriundos de plantas daninhas presentes em campos de produção de meloeiro - Rodrigues, Ana Paula Medeiros dos Santos (Brasil, 2017)
The Brazilian Northeast stands out in the national scenario, with the melon (Cucumis melo L.) cultivation as one of the activities of greater social and economic expression of region. Among the main problems faced by the producers are the diseases, among them, the melon collapse caused by Monosporascus cannonballus. Despite the importance of the disease, little is known about the variability of this pathogen. Aiming to investigate variability in M. cannonballus isolates from weeds in areas that produce melon, in the states of Rio Grande do Norte and Ceará. The research was divided into two stages: analysis of bredo and pinto-pinto isolates. Eighteen of Bredo (Trianthema portulacastrum L.) and pega-pinto (Boerhavia diffusa L.) isolates were evaluated for mycelial growth rate (MGR), number of perithecia (NP) and number of ascospores (NA) in different temperatures (20, 25, 30 and 35 ° C), salinity levels (0, 1, 4 and 8%), and pH levels (5.5, 6.0 and 8.0), as well as inhibition of mycelial growth to the fungicide fluazinam (IMGF), and to the serverity index of the disease to melon and watermelon (SID).. For the study of the bredo isolates, it was verified that the temperature of 30 ºC presented the highest values of MGR, whereas the one of 20 ºC the smaller ones. The highest values of NP were recorded in the temperature of 30ºC while that of 25ºC was the only one where there was ascospore production. The levels of 0 of 1% of salinity registered the highest values of MGR, and 8% of the lowest. NP values were only observed in the 0 and 1% salinity levels, with the highest values being 0%. Ascospores were only found at the 0% level. Levels of pH 5.5 and 6.0 provided the highest values of MGR, while 8.0 had the lowest values. Perithecias were observed at all pH levels, with level 6.0 giving the highest value. There was no ascospore production at any pH level. All isolates presented low sensitivity to fluazinam, with a mean of 15.53% IMGF. All isolates were pathogenic to melon and watermelon with mean SID of 56.25 and 70.13%, respectively. In multivariate analysis it was verified the formation of 4 similarity groups. For the study of pinto-pinto isolates, temperatures of 30 and 35 ºC showed the highest MGR values, while the lowest were at 20 ºC. The highest values of NP were recorded at temperatures of 30 and 35ºC while those at 25 and 30ºC were the only ones that presented ascospores. The salinity levels of 0 and 1% had the highest MGR values, while the lowest were at 8%. NP and NA values were observed only at the 0 and 1% salinity levels. Levels of pH 5.5 and 6.0 provided the highest values of MGR, while 8.0 had the lowest values. Perithecias were observed at all pH levels, with 6.0 being the highest value. Ascospores were observed at the levels of 5.5 and 6, 10 with 6 being the highest values. All isolates were sensitive to the fungicide fluazinam, with a mean of 19.76% IMGF. All isolates were pathogenic to melon and watermelon, except for MCp-09 that was not melon, with an average SID of 56.25 and 70.13%, respectively. In multivariate analysis it was verified the formation of 5 similarity groups. Isolates from the same area were distributed in different similarity groups, indicating high variability among the isolates. The occurrence of this high variability should be considered in melon breeding programs, avoiding that susceptible genotypes are considered resistant
Variability of Monosporascus cannonballus isolates from weeds in melon production fields
Keywords: Boerhavia diffusa L.; Cucumis melo; Fluazinam; Patógenos radiculares; Trianthema portulacastrum L.; Boerhavia diffusa L.; Cucumis melo; Fluazinam; Root pathogens; Trianthema portulacastrum L.; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA